Clinical features, treatment, and prognosis of 16 breast cancer patients with ocular metastases - Chang, Chunxiao; Shang, Yuhong; Gao, Yongsheng; Shang, Mao; Wang, Lizheng; Li, Huihui (Cellular and Molecular Biology, 2022)
The incidence of ocular metastases in patients with disseminated breast cancer is increasing. This study aimed to investigate the clinical features, treatment, and prognosis of breast cancer patients with ocular metastases. For this purpose, a total of 16 patients were diagnosed with ocular metastases. Demographic, treatment, and other clinical data were obtained from patients’ charts. The estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2) statuses of the patients were obtained from the histopathologic reports. Demographic features were analyzed through descriptive statistics, and the Kaplan–Meier method was used for survival analysis. The results showed that among the 16 patients (median age: 41 years), 10 had ER-positive, 8 had PR-positive, and 3 had HER2-positive disease. The choroid was the most commonly involved structure (n = 8). Nine (56%) patients had blurred vision. Treatments for these patients included systemic therapy (six patients), radiotherapy (three patients), and combined therapy (seven patients). The median time from the diagnosis of breast cancer to the diagnosis of ocular metastasis was 52.9 months, and the median time from the diagnosis of metastatic breast cancer at any other site to the diagnosis of ocular metastasis was 21.3 months. The median overall survival (OS) was 136.5 months (95% confidence interval, 40.6–232.4 months), and the median survival duration after ocular metastasis was 32.4 months (95% confidence interval, 20.1–44.7 months). The OS of patients with unilateral eye involvement and bilateral eye involvement did not differ significantly (P = 0.573), nor did the OS of those diagnosed before 2000 and in 2000 or later (P = 0.409). In general, a breast cancer patient with ocular metastasis can have a good prognosis after therapy. However, large-scale clinical studies are needed to confirm our findings.